A 60 yr record of atmospheric carbon monoxide reconstructed from Greenland firn air - Petrenko, Vasilii; Martinerie, P.; Novelli, P.; Etheridge, D. M.; Levin, Ingeborg; Wang, Z.; Blunier, T.; Chappellaz, J.; Kaiser, J.; Lang, P.; Steele, L. P.; Hammer, Samuel; et al. (Atmospheric chemistry and physics, 2013)
We present the first reconstruction of the Northern Hemisphere (NH) high latitude atmospheric carbon monoxide (CO) mole fraction from Greenland firn air. Firn air samples were collected at three deep ice core sites in Greenland (NGRIP in 2001, Summit in 2006 and NEEM in 2008). CO records from the three sites agree well with each other as well as with recent atmospheric measurements, indicating that CO is well preserved in the firn at these sites. CO atmospheric history was reconstructed back to the year 1950 from the measurements using a combination of two forward models of gas transport in firn and an inverse model. The reconstructed history suggests that Arctic CO in 1950 was 140–150 nmol mol−1, which is higher than today's values. CO mole fractions rose by 10–15 nmol mol−1 from 1950 to the 1970s and peaked in the 1970s or early 1980s, followed by a ≈ 30 nmol mol−1 decline to today's levels. We compare the CO history with the atmospheric histories of methane, light hydrocarbons, molecular hydrogen, CO stable isotopes and hydroxyl radicals (OH), as well as with published CO emission inventories and results of a historical run from a chemistry-transport model. We find that the reconstructed Greenland CO history cannot be reconciled with available emission inventories unless unrealistically large changes in OH are assumed. We argue that the available CO emission inventories strongly underestimate historical NH emissions, and fail to capture the emission decline starting in the late 1970s, which was most likely due to reduced emissions from road transportation in North America and Europe.
Gesehen am 20.01.2022